Evaluation of bacterial leakage of four root- end filling materials: Gray Pro Root MTA, White Pro Root MTA, Root MTA and Portland Cement (type I) - Zarabian M.; Aligholi M.; Shokouhi Nejad N (Tehran University of Medical Sciences, 2005)
Background and Aim: Today several materials have been used for root- end filling in endodontic surgery. Optimal properties of Pro Root MTA in in-vitro and in-vivo studies has been proven. On the other hand, based on some studies, Root MTA (Iranian Pro Root MTA) and Portland cement are similar to Pro Root MTA in physical and biologic properties. The aim of this study was to evaluate bacterial leakage (amount and mean leakage time) of four root- end filling materials. Materials and Methods: In this experimental in-vitro study, seventy six extracted single- rooted human teeth were randomly divided into six groups for root-end filling with gray Pro Root MTA, white Pro Root MTA, Root MTA (Iranian Pro Root MTA), Portland Cement (type I) and positive and negative control groups. Root canals were instrumented using the step- back technique. Root- end filling materials were placed in 3mm ultra sonic retro preparations. Samples and microleakage model system were sterilized in autoclave. The apical 3-4 mm of the roots were immersed in phenol red with 3% lactose broth culture medium. The coronal access of each specimen was inoculated every 24h with a suspension of Streptococcus sanguis (ATCC 10556). Culture media were observed every 24h for colour change indicating bacterial contamination for 60 days. Statistical analysis was performed using log- rank test with P<0.05 as the limit of significance. Results: At the end of study 50%, 56.25%, 56.25% and 50% of specimens filled with Gray Pro Root MTA, White Pro Root MTA. Root MTA and Portland Cement (type I) had evidence of leakage respectively. The mean leakage time was 37.19±6.29, 36.44±5.81, 37.69±5.97 and 34.81±6.67 days respectively. Statistical analysis of data showed no significant difference among the leakage (amount and mean leakage time) of the four tested root- end filling materials (P=0.9958). Conclusion: Based on the results of this study, there were no significant differences in leakage among the four tested groups at 60 days. The results suggest that Root MTA and Portland Cement can be used as less expensive root filling materials.